Quality of Life After Vestibular Schwannoma Surgery: A Question of Perspective - Bender, Miriam; Tatagiba, Marcos; Gharabaghi, Alireza (Frontiers in Oncology, 2022)
Objective: Health-related quality of life (HRQoL) and self-reported outcome measures have a relevant impact on the medical decision-making process. They capture either the current status and allow for multiple prospective evaluations in the course of a treatment or rely on the patients’ retrospective comparison of health before and after an intervention to assess its benefit. Importantly, these patient-assessed measures may be influenced by psychological factors. We compared HRQoL and perceived benefit in the course of surgical vestibular schwannoma (VS) treatment, as assessed by the patients from a prospective and retrospective point-of-view, and evaluated the influence of co-morbid depression. Methods: Within a prospective observational single-center study, forty-three patients with VS were investigated before and after retrosigmoid tumor resection. SF-36, Beck Depression Inventory and patient-assessed clinical symptoms were acquired before surgery and at follow-up. At follow-up, the Glasgow Benefit Inventory (GBI) was acquired as well. Results: SF-36 scores were significantly lower than the age and sex matched normative data in six and three out of eight categories before and after surgery, respectively. Three categories improved significantly after vs. before surgery; one of them (global health) reached a minimal clinical important difference. In contrast, patients reported predominantly a deterioration, when asked for a retrospective evaluation of the benefit (i.e., GBI). Depression correlated with both SF-36 and GBI, determined dissatisfaction, improved significantly after surgery and was the measure that had the largest impact on HRQoL. Conclusion: Prospective and retrospective HRQoL measures may lead to different findings and can be confounded by psychological factors.